What Might It Mean to Live Well With Depression? - Scrutton, Anastasia Philippa (Journal of disability & religion, 2016)
It is well recognized that people live well with a number of illnesses. It is also well recognized that some people who have had depression in the past regard it as having given rise to positive present characteristics and experiences. However, because of its nature, depression poses a particularly difficult case for the idea of living well during the experience of depression itself. This article looks at characteristics and experiences that could be described as living well found in some autobiographies of depression, focusing on three themes: living faithfully, cultivating particular forms of compassion, and developing a heightened appreciation of beauty. The aim is not to describe what will or should happen in all experiences of depression, but to draw and pay attention to some hopeful experiences.